On Languages Generated by Signed Grammars - Egccioglu, Omer; Nagy, Benedek (Open Publ Assoc, 2023)
We consider languages defined by signed grammars which are similar to context-free grammars except productions with signs associated to them are allowed. As a consequence, the words generated also have signs. We use the structure of the formal series of yields of all derivation trees over such a grammar as a method of specifying a formal language and study properties of the resulting family of languages.
27th International Conference of the Implementation and Application of Automata (CIAA) -- SEP 19-22, 2023 -- Famagusta, CYPRUS
Keywords: Ambiguity